2008
DOI: 10.1074/jbc.m800911200
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Residues Interacting with Both the Bound Quinone and Coenzyme, Pyrroloquinoline Quinone, in Escherichia coli Membrane-bound Glucose Dehydrogenase

Abstract: The Escherichia coli membrane-bound glucose dehydrogenase (mGDH) as the primary component of the respiratory chain possesses a tightly bound ubiquinone (UQ) flanking pyrroloquinoline quinone (PQQ) as a coenzyme. Several mutants for Asp-354, Asp-466, and Lys-493, located close to PQQ, that were constructed by site-specific mutagenesis were characterized by enzymatic, pulse radiolysis, and EPR analyses. These mutants retained almost no dehydrogenase activity or ability of PQQ reduction. CD and high pressure liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…The characteristics of the spectrum appear to consist of a broad signal with the peak-to-peak line width of nearly 100 G and a small signal at g ϭ 2.004 (at ϳ3400 G) with that of nearly 10 G (Ref. 25 and Fig. 4A).…”
Section: Epr Of Uq-and Mq-bearing Mgdhs-mentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of the spectrum appear to consist of a broad signal with the peak-to-peak line width of nearly 100 G and a small signal at g ϭ 2.004 (at ϳ3400 G) with that of nearly 10 G (Ref. 25 and Fig. 4A).…”
Section: Epr Of Uq-and Mq-bearing Mgdhs-mentioning
confidence: 99%
“…Although its tertiary structure has not been determined, the arrangement of amino acid residues around PQQ has been modeled (19) and has been confirmed by results of several experiments with site-directed amino acid substitutions (20 -24). The substitution of either Lys-493, which is modeled to hydrogen-bond to an orthoquinone portion of PQQ as a vital part for the catalytic reaction, or Asp-466, which is located close to that portion and functions in extraction of a proton from substrate glucose, has a severe effect on the catalytic ability of the enzyme (24,25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6). Pulse radiolysis analysis revealed that the two redox centers are closely located at a distance of 11-13 Å and that Asp466 and Lys493 are involved in proton donation to the semiquinone anion radical of bound Q and in electron transfer from bound UQ to PQQ, respectively (Elias et al, 2000;Mustafa et al, 2008a). Recent mGDH analysis provided the first evidence that the primary dehydrogenase in respiratory chains utilizes both MK and UQ as a bound Q and suggest that bound MK occurs in a fashion similar to that of bound UQ in the mGDH molecule and functions as an electron acceptor from PQQ (Mustafa et al, 2008b).…”
Section: Menaquinone As Well As Uq As a Bound Quinone Is Crucial For mentioning
confidence: 99%
“…PQQ prevents accumulation of alpha-synuclein and amyloid beta proteins [103]. PQQ provides advanced level of protection on endothelial cells of mouse brain from Gluco-damage by suppression of ROS and cell death by blocking signaling pathway of JNK [104][105][106][107].The treatment of proliferated Schwann cells with various concentrations of PQQ enhanced the expression of CREB, c-fos, c-jun and PCNA [108]. PQQ on traumatic brain injury (TBI) has found to be neuroprotective [109] as measurements of physiological parameters indicated that PQQ restrains function of brain in older people related attention, working and memory [110].…”
Section: Pqq In Neurological Injury and Repairmentioning
confidence: 99%